THE ROLE OF PLOT AND COMPOSITION IN MIND IMAGERY (IN THE EXAMPLE OF THE STORIES "JEALOUSY", "WOMAN") - Rakhmatova Rayhona Mirzohid Kizi (European Journal of Humanities and Educational Advancements, 2023)
the article talks about the plot, composition, image of the psyche, the importance of the plot and composition in revealing the psyche of the hero, the role of composition and plot elements in stories and similar issues.